Effects of cheerleading practice on advanced glycation end products, areal bone mineral density, and physical fitness in female adolescents - Wang, Lijun; Zhang, Hongli; Xu, Tuo; Zhang, Jing; Liu, Yuanyuan; Qu, Yue (Frontiers in Physiology, 2022)
Background: Exercise has been widely reported to promote bone health, but it is unknown whether is associated with a reduction in advanced glycosylation end products (AGEs). This study aimed to investigate the effects of 14 weeks of cheerleading practice on bone mineral density (BMD) and AGEs Methods: In this study, 46 female teenagers (age, 19.52 ± 1.21 yr; body mass index, 20.15 ± 2.47 kg/m2) were randomly divided into a cheerleading group (CHE, n = 21) and a control group (CON, n = 25). The CHE group was subjected to cheerleading practice twice a week for 14 weeks; the CON group maintained their daily routine. Participants' AGEs, BMD, physical fitness, physical activity, eating behavior, exercise enjoyment, and mental health were investigated. Results: After 14 weeks of intervention, 1) BMD and its T-value increased significantly in both groups with significantly higher increases in the CHE group (p < 0.05). 2) AGEs significantly decreased in the CHE group (-2.7%), but not in the CON group (p > 0.05). 3) Vertical jumps and sit-ups significantly increased in the CHE group (p < 0.05), but not in the CON group (p > 0.05). 4) ΔAF values was significantly negatively correlated with Δ BMD and T-value of post-exercise BMD (r = -0.302, r = -0.380, p < 0.05). 5) ΔAF values mediated the effect of exercise on the T-value of the BMD (indirect effect: 0.079, 95% CI 0.014 - 0.159). Conclusion: Cheerleading practice improved BMD and physical fitness and reduced AGEs accumulation in female adolescents. The effect of exercise on BMD was partially mediated by AGEs.